Narrative Spaces in the Novel "Dusk of the Cranes" by Saad Muhammad Rahim (Journal of the College of Basic Education, 2026)
The concept of narrative space opens up to profound symbolic themes that aimed to Inspective access to the system of internal relationships of the narrative text, enabling the reader to discover uninterpreted visionary spaces and thus reap an additional productive harvest to understand that space and perceive its intentional processes through the formative system of the narrative world. From this standpoint, in this research, we attempt to monitor the transformations of narrative space in the novel "Dusk of the Cranes" by the Iraqi novelist Saad Muhammad Rahim, in a atypical reading, transcending the problems of the prevailing systematic understanding by opening up to the intentions of narrative space and its active structures in that novel, which represents an imagined reduction of an important stage in the history of modern Iraq